REPRESENTASI PEMANFAATAN MEDIA SOSIAL SEBAGAI MEDIA LITERASI TENTANG ANTISIPASI CYBERCRIME (STUDI DESKRIPTIF PADA AKUN MALAMTANPAKATA) - Fauziah Fauziah (Commed Jurnal Komunikasi dan Media, 2026)
Social media Twitter is a social media that is currently popular again after it was previously popular in 2011. With the presence of Twitter, an issue can become a viral phenomenon when it gets a lot of attention from Twitter social media users. Through a thread on Twitter, the user could tell the story of the event and the chronology in detail. One of them is the chronology of crimes that happen in the virtual world, namely lovescam which is currently called tinder swindler inspired by the Netflix series called "The Tinder Swindler". Crimes in the world like tinder swindlers must also be exposed through social media, one of which is Twitter with the feature it has, namely threads. The purpose of this research is to know how the user interacts with Twitter in the thread of fraud by tinder swindlers on malamtanpakata account. Analyzing the data that the researcher did is with the observation of each dialog for Twitter users that happened in the thread on malamtanpakata account. From the analysis done on the case thread fraud tinder swindler generate traffic information user twitter that is the basic pattern of communication conversation.